Legal Culture of Customary Inheritance Division in the Sasak Community: A Review from the Perspective of Legal Plurality and Islamic Legal Anthropology - Syibly, M. Roem; Walijah, Nurhasanah (Unisia, 2024)
This study aims to discuss the legal culture of inheritance distribution in a Sasak community in Jerowaru Village, Lombok by reveal the interaction of customary law and Islamic law used in distributing inheritance. This study is a qualitative descriptive which considers normative legal research and empirical legal research, as well as Islamic law anthropology and legal pluralism perspective. Qualitative data was collected by conducting in depth interviews with religious leaders, traditional leaders and community members. Number three: Sasak community has a pattern of heritage distribution (inheritance distribution) in the form of "Sak Mame Belembah Sak Nine Bereson" sons get more than daughters. It illustrates the give and take of customary law with its emphasis on social equilibrium and family responsibility, together with Islamic legal practices tailored to local realities. The analysis by Griffiths and Hooker in legal pluralism theory, as well as from Clifford Geertz and John Bowen in Islamic legal anthropology, shows that the law in the Sasak community has appeared not static law but dynamic law, which is responsive against social change. Inheritance law integrates customary law, and Islamic law eventually produces an inheritance legal system that is broad and flexibly ensures substantive and distributive justice; one way is to amalgamate cultural values and religious needs embraced by the society. To its academic contribution, this research is an answer revealing how complex the legal dynamics are in a plural societies context, and there is a new way of looking to create Islamic Law in line with Consuetudo Law to build a legal system that is fair and responsive by referring to local wisdom.